The Earth, the City, and the Hidden Narrative of Race - Anthony, Carl (Book collections on Project MUSE., 2017)
"Carl Anthony's memoir interweaves urban history, racial justice, and cosmology with personal experiences as an architect/planner, environmentalist, and Black American. By connecting struggles for social and racial justice to the Universe Story, it creates new story for our time"--